Public and private sector roles in agricultural research : theory and experience - Umali, Dina L. (World Bank WashingtonUS, 1992)
Analyzes the economic nature of the different functional and commodity areas in agricultural research, the results of which are used to generate a framework for establishing the appropriate roles for the various participants in the research sector (public institutes, universities, nonprofit organizations, and the private sector).